ONTOLOGY-BASED APPROACH FOR AUTOMATED INFORMATION RETRIEVAL SYSTEMS: PRINCIPLES AND APPLICATIONS - Muxtarov Rustam Axtam o‘g‘li (SCIENCE AND CULTURE: INNOVATIONS OF THE 21ST CENTURY, 2026)
This article explores the use of ontology-based approaches in automated information retrieval (IR) systems. Ontologies provide a structured representation of domain knowledge, enabling IR systems to understand, interpret, and process user queries more effectively. By integrating ontologies into automated search systems, semantic consistency, relevance, and accuracy of retrieved information can be significantly enhanced. The paper discusses the principles, methodologies, and practical applications of ontology-driven IR, demonstrating its role in improving search efficiency, knowledge discovery, and intelligent decision support in modern information systems.